(untitled) (Andamios, Revista de Investigación Social, 2014)
The present work tries to offer an approximation to the expression “lacanian left”. This one has turned into a common place for the revitalización of the left political thought in the beginning of the 21st century. Concretely we try to gather the presence of two ways for going to the matter, geopolitic and idiomatically distanced. It will allow us to distinguish between an offer arisen in Universities of United Kingdom (context of Essex’s School), and other one more connected to authors in Latin-America and Spain. The different implications will be valued to think the social transformation and the renovation of the political subject theory.